Homo brevis. Ethics of duration, fatigue and the end - Innerarity, Daniel (Estudios de Filosofía, 1996)
As life, to which it is intended, philosophy must be brief This idea must restrict the very dominant universal and timeless character of Philosophical Ethics in its conception of virtue and law. Three aspects are examined. First, the temporal condition of human life, particularly positive consequences of such briefness. Second, the fact that beginnings and endings as context of human life are out of our control. And third, the anthropological sense of fatigue; this is, the idea that if good life must be carried out within time, and not despite it, the role of moral reflection is lo avoid two risks for human beings: overrating and undervaluing.